2010
DOI: 10.1002/jobm.201000098
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and phylogeny of plant growth‐promoting bacilli from moderately acidic soil

Abstract: The molecular diversity of aerobic endospore-forming bacteria, typically Bacillus and its derived genera, has been investigated in various environments. However, there have been few investigations concerning Bacillus in acidic soils. In this study, the genotypic diversity and phylogenetic relationships among plant growth-promoting (PGP) bacilli isolated from the rice rhizosphere growing in acidic soils of Kerala (pH varying from 6.3 to 6.8) were investigated. For assessing their biocontrol potential and PGP at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 46 publications
0
45
0
1
Order By: Relevance
“…B3 was able to utilize only 35.71% of the substrates tested. Strains of Bacillus pumilus generally show high resistance to environmental stresses, including UV light exposure, desiccation, and the presence of oxidizers such as hydrogen peroxide and produce compounds antagonist to fungal and bacterial pathogens [17]. In the present investigation, this strain was able to show growth on 45% of the substrates and chemical agents tested, besides being uniquely able to use D-Arabitol, and uniquely exhibiting resistance to guanidine and sodium butyrate (Table 3).…”
Section: Biochemical Tests and Substrate Utilization Profiles For Selmentioning
confidence: 57%
See 2 more Smart Citations
“…B3 was able to utilize only 35.71% of the substrates tested. Strains of Bacillus pumilus generally show high resistance to environmental stresses, including UV light exposure, desiccation, and the presence of oxidizers such as hydrogen peroxide and produce compounds antagonist to fungal and bacterial pathogens [17]. In the present investigation, this strain was able to show growth on 45% of the substrates and chemical agents tested, besides being uniquely able to use D-Arabitol, and uniquely exhibiting resistance to guanidine and sodium butyrate (Table 3).…”
Section: Biochemical Tests and Substrate Utilization Profiles For Selmentioning
confidence: 57%
“…At 90% similarity level, thermotolerant isolates from Bakreshwar, Balrampur, Chumathang and Vashist thermal springs grouped into 14, 14, 11 and 9 clusters respectively. ARDRA has been effectively utilized in the past for both culture dependent and culture independent diversity studies as a tool to group the isolates and clones into phylotypes [17][18][19].…”
Section: Amplified Rdna Restriction Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, many Bacillus strains have been exploited for biotechnological applications (Hou et al, 2005) and have been shown to contribute to the promotion of plant growth (Yadav et al, 2011). Thus, the transport of airborne bacteria provides a mechanism for the dispersal of bacterial populations that can have both beneficial and negative influences on human health and plant growth.…”
Section: Influences Of Bacterial Communities On Ecosystems and Human mentioning
confidence: 99%
“…diduga menjadi dominan pada kondisi lingkungan yang ekstrim. Yadav et al (2011) menyebutkan bahwa genus Bacillus mempunyai rentang keragaman spesies yang dominan pada berbagai kondisi lingkungan termasuk pada kondisi lingkungan yang ekstrim. Tidak hanya pada kondisi tanah yang ekstrim, Bacillus juga menjadi jenis yang dominan ditemukan pada makanan yang dibuat dengan proses fermentasi dengan kondisi asam yang tinggi (Kim et al, 2014).…”
Section: Hasil Dan Pembahasanunclassified